EFEKTIVITAS DECANTER SOLID DAN POC KULIT PISANG DALAM MENINGKATKAN PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max (L.) Merril) - rajagukguk, Wina Apriyani; Duaja, Made Deviani; Mukhsin, Mukhsin (Jurnal Agroecotania : Publikasi Nasional Ilmu Budidaya Pertanian, 2025)
ABSTRACT The application of solid decanter and banana peel POC can be a solution to improve soil quality in an effort to increase the growth and yield of soybeans. This study aims to examine the interaction of the application of solid decanter and banana peel POC as well as determine the optimal dose of solid decanter and the concentration of banana peel POC that increases the growth and yield of soybeans. This research was conducted at the Experimental and Research Garden of the Faculty of Agriculture, University of Jambi, Mendalo Indah Village from March to July 2025. This research uses a Random Group Design consisting of 2 factors. The first factor: solid decanter (d), which consists of 3 levels, namely 5 tons/ha, 10 tons/ha, 15 tons/ha. The second factor: POC of banana peel, which consists of three levels, namely 10%, 30%, 50%. Thus, there are nine treatment combinations with three repetitions. Observed variables include plant height, number of leaves, number of pods per plant, seed weight per plant, weight of 100 seeds, yield per hectare. The results showed that there was no interaction between all the variables observed. However, the application of 10 tons/ha of solid decanter has a real effect on plant height, number of leaves, number of fruits per plant, seed weight per plant, yield per hectare and giving 30% POC banana peel has a real effect on the number of leaves and yield per hectare. Keywords: Solid Decanter, Soybean, Banana Peel POC